Handling and reporting of orchidectomy specimens with testicular cancer: areas of consensus and variation among 25 experts and 225 European pathologists. Issue 3 (17th March 2015) - Berney, Daniel M; Algaba, Ferran; Amin, Mahul; Delahunt, Brett; Compérat, Eva; Epstein, Jonathan I; Humphrey, Peter; Idrees, Mohammed; Lopez‐Beltran, Antonio; Magi‐Galluzzi, Cristina; Mikuz, Gregor; Montironi, Rodolfo; et al.
<x xml:space="preserve">Abstract</x> Aims The handling and reporting of testicular tumours is difficult due to their rarity. Methods and results A survey developed by the European Network of Uro‐Pathology (ENUP) and sent to its members and experts to assess the evaluation of testicular germ cell tumours. Twenty‐five experts and 225 ENUP members replied. Areas of disagreement included immaturity in teratomas, reported by 32% of experts but 68% of ENUP. Although the presence of rete testis invasion was reported widely, the distinction between pagetoid and stromal invasion was made by 96% of experts but only 63% of ENUP. Immunohistochemistry was used in more than 50% of cases by 68% of ENUP and 12% of experts. Staging revealed the greatest areas of disagreement. Invasion of the tunica vaginalis without vascular invasion was interpreted as T1 by 52% of experts and 67% of ENUP, but T2 by the remainder. Tumour invading the hilar adipose tissue adjacent to the epididymis without vascular invasion was interpreted as T1: 40% of experts, 43% of ENUP; T2: 36% of experts, 30% of ENUP; and T3: 24% of experts, 27% of ENUP. Conclusions There is remarkable consensus in many areas of testicular pathology. Significant areas of disagreement included staging and reporting of histological types, both of which have the potential to impact on therapy.